2005
DOI: 10.1038/sj.embor.7400550
|View full text |Cite
|
Sign up to set email alerts
|

A molecular switch and electronic circuit modulate catalase activity in catalase‐peroxidases

Abstract: The catalase reaction of catalase‐peroxidases involves catalase‐specific features built into a peroxidase core. An arginine, 20 Å from the active‐site heme, acts as a molecular switch moving between two conformations, one that activates heme oxidation and one that activates oxoferryl heme reduction by H2O2, facilitating the catalatic pathway in a peroxidase. The influence of the arginine is imparted to the heme through its association with or dissociation from a tyrosinate that modulates reactivity through a M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 33 publications
6
74
0
1
Order By: Relevance
“…Interestingly, this adduct can be associated with a KatG-typical arginine (R439) [2]. Its association with the tyrosinate ion on the adduct is also required for optimum catalatic rates [19,23]. Another important residue at the distal heme cavity is D152, which is part of the substrate channel and has its side chain carboxyl group pointing toward the heme pocket.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this adduct can be associated with a KatG-typical arginine (R439) [2]. Its association with the tyrosinate ion on the adduct is also required for optimum catalatic rates [19,23]. Another important residue at the distal heme cavity is D152, which is part of the substrate channel and has its side chain carboxyl group pointing toward the heme pocket.…”
Section: Resultsmentioning
confidence: 99%
“…We found GPx activity in low-and moderate-dose α-amanitin poisoning to be slightly higher than in the controls, but its activity was the same in moderate-and high-dose poisoning groups. In the current literature, investigators have tended not to evaluate hepatocyte GPx activity in α-amanitin poisoning, because they indicated that GPx was responsible for decomposition of H 2 O 2 at low levels of H 2 O 2 and that CAT was responsible at high levels of H 2 O 2 (15,16,29). Conversely, it has been reported that increased ROS load and decreased glutathione levels might play an important role in hepatocyte necrosis induced by toxins, including paracetamol and α-amanitin (26,30 production due to increased SOD activity, and GPx was also involved in the antioxidant mechanisms fighting against an increased ROS load.…”
Section: Histopathological Assessmentmentioning
confidence: 99%
“…3 (B)) while D125 has been known to be important in thefrom H 2 O 2 , respectively. Hence, the mobile D125 residue will also be suggestive of utilizing as either initiator H 2 O 2 or substrate ODA recognition, making it effective in binding substrate, though disruption of π-complexes with heme and W95 known to act on as molecular switch from the catalase to the peroxidase (Carpena et al, 2005). The amino N of backbone I217 forms an H-bond to the oxygen O 1 of carbonyl group of the side D125.…”
Section: Methodsmentioning
confidence: 99%
“…The aromatic substrate binding site on heme iron has been identified by determining the structures of [S305A] and its complexes with SHA. These provide a complete description of substrate binding in KatG (Sato et al, 2011b;2011c (Carpena et al, 2005;Jakopitsch et al, 2004;Ghiladi et al, 2004). One of the commonest causes of resistance about INH is also the [R409L] mutation in MtKatG and known for peroxidase reaction (Ghiladi et al, 2004;Saint-joanis et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation